MAKNA POLA IKAT PADA TARI JEPIN TALI BINTANG DI DESA KALIMAS KECAMATAN SUNGAI KAKAP KABUPATEN KUBURAYA - Rulli Yandi; Regaria Tindarika; Asfar Muniir (Universitas Tanjungpura, 2021)
AbstractThis research is motivated to describe a complete data and information about the Tari Jepin Tali Bintang. The reason the researchers studied the Jepin Tali Bintang dance was because of the uniqueness of this dance. The uniqueness lies in the process of weaving the rope, in which the weaving process produces several patterns and forms a binding bond, and the process of opening the rope is used a faster tempo than when weaving the rope. In this study, the method used is descriptive analysis, the form used is a qualitative form, the approach used is a semiotic approach. The the respondent in this research were artist knew about the Jepin dance The meaning of “Tari Jepin Tali Bintang” the tie pattern the village of Kalimas Kakap river district Kuburaya district. The data in this research collected by the several techniques such as observations, interviews and documentation studies. The data validity testing technique used was the extension of the observation and triangulation. Based on the analysis of the data it was concluded that there are three bond patterns, tie knot pattern, cross tie pattern, earth loop tie pattern. The movements in this dance are hanging steps and intermittent steps.Keywords: Meaning of the tie patterns, Tari Jepin Tali Bintang